Risk Factors of Stationarity of Brucellosis Among Animals and Humans (Bangladesh Journal of Infectious Diseases, 2024)
Background: Brucellosis is an infectious bacterial disease with significant epizootic and epidemiological impact, affecting both animals and humans. The disease is particularly prevalent in regions with extensive livestock farming, leading to considerable economic and social harm. The persistence of brucellosis in certain areas, despite preventive measures, necessitates further investigation into the risk factors contributing to its stationarity.Objective: The study aims to identify and analyze the risk factors contributing to the stationary presence of brucellosis among animals and humans in the Zhany-Zher village, Sokuluk district, Kyrgyz Republic, over a six-year period.Methodology: Epizootological studies were conducted on the incidence of brucellosis in animals and humans on a farm in Zhany-Zher over six years (2018-2023). Data were collected from serological studies of blood from cows and milk samples. The study also included a survey of private farms and analysis of veterinary and economic activities. The results were presented in both tabular and graphical formats.Results: The analysis of serological studies indicated that brucellosis was detected annually among cows in Zhany-Zher, with the percentage of positive cases ranging from 2.17% to 12.02%. The highest rate of positive cases was observed in 2022, attributed to reduced diagnostic efforts during the COVID-19 pandemic. Brucellosis was also detected in other animals, including dogs, and human cases were reported annually.Conclusion: The stationary nature of brucellosis in Zhany-Zher is maintained by various risk factors, including uncontrolled movement of livestock, inadequate serological examination of fattening bulls, and the presence of pets that may act as carriers of the disease. Effective management requires strict monitoring of livestock transactions, regular diagnostic testing, and public education on brucellosis.Bangladesh Journal of Infectious Diseases, June 2024;11(1):38-44